The Effectiveness of Articulation Therapy through Telepractice for Children with Cerebral Palsy Inclusive Schools - Gunawan Gunawan; Kliwon Kliwon (Green Publisher Indonesia, 2022)
The purpose of this study is providing information on the effectiveness of articulation therapy through telepractice for children with cerebral palsy at inclusive schools in Surakarta. This study uses the survey method, aiming to find information that will be used to solve problems and not to test hypotheses. The subjects of this study were all children with cerebral palsy in inclusive schools in Surakarta. The instrument in this study is in the form of Articulation Test Guidelines on the consonant /r/ followed by vowel sounds [ /a/, /i/, /u/e/, /e/ and /o] initial, middle and final positions in the form of words with the help of pictures. Therapeutic tools used in intervening with children are computers, cellphones with video calls. This research is required to be one of the models of Intervention/Management of Articulation Therapy through Telepractice for Children with Cerebral Palsy in Inclusive Schools. Based on the results of the analysis using the marginal homogeneity test, a p value of 0.031 (p < 0.05) statistically showed that there was a difference between before and after telepractice articulation therapy for cerebral palsy students in inclusive schools in Surakarta